Defining Pathogenic Bacterial Species in the Genomic Era - Georgiades, Kalliopi; Raoult, Didier (Frontiers in Microbiology, 2011)
Actual definitions of bacterial species are limited due to the current criteria of definition and the use of restrictive genetic tools. The 16S rRNA sequence, for example, has been widely used as a marker for phylogenetic analyses; however, its use often leads to misleading species definitions. According to the first genetic studies, removing a certain number of genes from pathogenic bacteria removes their capacity to infect hosts. However, more recent studies have demonstrated that the specialization of bacteria in eukaryotic cells is associated with massive gene loss, especially for allopatric endosymbionts that have been isolated for a long time in an intracellular niche. Indeed, sympatric free-living bacteria often have bigger genomes and exhibit greater resistance and plasticity and constitute species complexes rather than true species. Specialists, such as pathogenic bacteria, escape these bacterial complexes and colonize a niche, thereby gaining a species name. Their specialization allows them to become allopatric, and their gene losses eventually favor reductive genome evolution. A pathogenic species is characterized by a gene repertoire that is defined not only by genes that are present but also by those that are lacking. It is likely that current bacterial pathogens will disappear soon and be replaced by new ones that will emerge from bacterial complexes that are already in contact with humans.